Antibody expression and production - Al-Rubeai, Mohamed (Springer eBooks., 2011)
Engineered antibodies currently represent over 30% of biopharmaceuticals in clinical trials and their total worldwide sales continue to increase significantly. The importance of antibody applications is reflected in their increasing clinical and industrial applications as well as in the progression of established and emerging production strategies. This volume provides detailed coverage of the generation, optimization, characterization, production and applications of antibody. It provides the necessary theoretical background and description of methods for the expression of antibody in microbial and animal cell cultures and in transgenic animals and plants. There is a strong focus on those issues related to the production of intrabodies, bispecific antibody and antibody fragments and also to novel applications in cancer immunotherapy.